RUSSIAN STRATEGY OF ENTERING THE INNOVATION MARKETS OF THE MIDDLE EAST - D. A. Maryasis (Vestnik MGIMO-Universiteta)
This article is an attempt to formulate a non-standard multifactor approach to the problem of consolidating Russia’s presence in the countries of the Middle East. It explores the possibility of creating in the Arab countries a system of educational courses related to innovation. These courses will make it possible for young people in the region to form an attitude towards our country as one of the leaders in the high-tech economy, to strengthen their loyalty to representatives of domestic business. In the future, the ecosystem of innovations can be formed as a result of educational efforts. That is going to allow Russian business circles to take part in the commercialization of new technologies created by innovators of the region. Russia’s innovative presence in the Middle East region can be embodied in the form of joint ventures, the outsourcing of a number of industries and the provision of technological services as well as joint applied scientific research. Such efforts will bring changes in the existing international division of labor by creating more favorable conditions for the development of the economy of the Russian Federation and its transition to the economy of innovation. Moreover, the article draws attention to the possibility of cooperation between Russia and Israel for the organization of a platform for effective interaction between representatives of innovative communities of Muslim countries of the Middle East and participants of the high technology market of the Jewish state. The article shows that the implementation of such a strategy will allow our country to become meaningful player in the process of economic and socio-political transformation of the region. The promotion of innovative business in the region should be part of a wider strategy for promoting a positive image of Russia, creating economic grounds for existing political and military-political ties with the countries of the Middle East.